Sensemaking as a Cultural Practice in Managing Communication Ambiguity Organization: An Organizational Ethnographic Study at Prospect Institute - Arliza Farah Az Zahra; Alfian Muhazir; Dias Regian Pinkan (Jogjakarta Communication Conference (JCC), 2026)
The ability of an organization to interpret ambiguous situations is an important factor in maintaining effective communication and work coordination amidst the increasingly complex dynamics of the organization. The development of the work environment, characterized bt the rapid flow of information, cross-functional interactions, and collaboration among organizational members, increases the potential for ambiguity in communication. These conditions require organizations to have interpretation mechanisms that enable each member to understand information more clearly and build a shared understanding in carrying out work activities. In this study, the sensemaking process is important as a collective effort that enables organizational members to interpret information, clarify the meaning of messages, and align their understanding of the work situation they are facing. This study aims to analyze how sensemaking occurs within the organizational culture at Prospect Institute, particularly in addressing potential communication ambiguities that arise in interactions between members and between divisions. This research uses a qualitative approach with organizational ethnography methods to gain a deep understanding of communication experiences that occur in daily work practices. Data collection was conducted thru in-depth interviews with employes who are directly involved in work activities and organizational coordination processes. The research results indicate thet the organizational culture at Prospect Institute reflects meaning-making practices supported by relatively clear coordibation patterns among the organization’s members. When information is considered ambiguous, organizational members actively seek confirmation thru discussion and direct clarification to ensure a shared understanding. This practice is also evident in the adaptation process for new members, where the organization does not allow new employes to interpret information speculatively, but rather encourages a process of joint explanation and verification to minimize potential misunderstandings. The findings of this research indicate that sensemaking not only functions as an individual interpretation process but also as an organizational cultural practice that strengthens coordination, maintains clarity of communication, and supports the formation of collective understanding in daily work activities. Practically, the results of this research contribute to the Prospect Institute by strengthening organizational communication practices based on clarification, open coordination, and shared learning among organizational members.